Long-Term Antithrombotic Treatments Prescribed for Cardiovascular Diseases in Patients with Hemophilia: Results from the French Registry - Guillet, Benoît; Cayla, Guillaume; Lebreton, Aurélien; Trillot, Nathalie; Wibaut, Bénédicte; Falaise, Céline; Castet, Sabine; Gautier, Philippe; Claeyssens, Ségolène; Schved, Jean-François (Thrombosis and Haemostasis, 2020)
Cardiovascular diseases (CVDs) are a major issue in aging patients with hemophilia (PWHs). Antithrombotic agents are widely used in the general population for CVD treatment, but this recommendation is not fully applicable to PWHs. To improve treatment strategies, a prospective case–control study (COCHE) that analyzed CVD management and follow-up (2 years/patient) in PWHs was performed in France from 2011 to 2018. In total, 68 PWHs (median age: 65 years [39–89]; 48 mild, 10 moderate, and 10 severe hemophilia) were included (n = 50 with acute coronary syndrome, n = 17 with atrial fibrillation, n = 1 with both). They were matched with 68 control PWHs without antithrombotic treatment. In our series, bleeding was significantly influenced by (1) hemophilia severity, with a mean annualized bleeding ratio significantly higher in COCHE patients than in controls with basal clotting factor level up to 20%, (2) antihemorrhagic regimen (on-demand vs. prophylaxis) in severe (hazard ratio [HR] = 16.69 [95% confidence interval, CI: 8.2–47.26]; p < 0.0001) and moderate hemophilia (HR = 42.43 [95% CI: 1.86–966.1]; p = 0.0028), (3) type of antithrombotic treatment in mild hemophilia, with a significantly higher risk of bleeding in COCHE patients than in controls for dual-pathway therapy (HR = 15.64 [95% CI: 1.57–115.8]; p = 0.019), anticoagulant drugs alone (HR = 9.91 [95% CI: 1.34–73.47]; p = 0.0248), dual antiplatelet therapy (HR = 5.31 [95% CI: 1.23–22.92]; p = 0.0252), and single antiplatelet therapy (HR = 3.76 [95% CI: 1.13–12.55]; p = 0.0313); and (4) HAS-BLED score ≥3 (odds ratio [OR] = 33 [95% CI: 1.43–761.2]; p = 0.0065). Gastrointestinal bleeding was also significantly higher in COCHE patients than in controls (OR = 15 [95% CI: 1.84–268]; p = 0.0141). The COCHE study confirmed that antithrombotic treatments in PWHs are associated with increased bleeding rates in function of hemophilia-specific factors and also of known factors in the general population.
Keywords: antithrombotic treatment; atrial fibrillation; cardiovascular disease; hemophilia; bleeding risk